Tritium in fish from remote lakes in northwestern Ontario, Canada. (December 2018) - Kim, S.B.; Rowan, D.; Chen, J.; Rodgers, C.M.C.; Rennie, M.D.
Abstract: Tritium is most commonly generated as a by-product of nuclear reactors. As such, environmental concentrations are typically only reported near regions of interest, and background concentrations in areas unaffected by anthropogenic disturbance are not well characterized. To provide information on background levels of tritium in the natural environment, tissue-free water tritium (TFWT) and organically-bound tritium (OBT) were measured in the flesh of 106 fish collected within three lakes located at the IISD-Experimental Lakes Area (ELA) in Ontario, Canada in 2014. For the three ELA lakes studied, water tritium (HTO) activity concentration was determined to be below reliably detectable levels (0.6 Bq/L). Fish TFWT was found to be below 0.7 Bq/L, similar to the surrounding water tritium activity concentration. Fish OBT activity concentrations, at below 5 Bq/L, were also very low. Fish size was significantly related to OBT activity in Lake Whitefish and White Sucker from Lake 302, but not in other lakes. Though we observed significant differences in potential tritium exposure to humans among lakes, the levels of tritium reported here are below the Canadian natural background radiation of 1.8 mSv/y. These results provide information on background levels of tritium in freshwater fishes in Canada. Highlights: Investigate information on background levels of tritium in the natural environment at the Experimental Lakes Area (ELA). Fish TFWT was to be below 0.7 Bq/L, which was a similar to the surrounding water tritium activity concentration. Fish size was considerably related to OBT activity in Lake Whitefish and White Sucker from Lake 302.